Marketing and Rural Entrepreneurship in Amealco, actions to improve the situation of artisans - Velázquez Hernández, Jorge Arturo; Alonso Chombo, Rosalía; Romero Zepeda, Jorge Adán (Advances in Social Sciences Research Journal, 2021)
Currently, marketing is a tool that helps entrepreneurs to promote their products and improve the situation they have in the business sector based on the various tools that exist to optimize their image and sales. This research aims to elucidate the importance of marketing in the professional development of artisans in the municipality of Amealco. It seeks to recognize that micro and small businesses dedicated to the sale of handicrafts need to make adequate and efficient use of the various marketing tools that exist to improve their current situation. The results obtained in the field work allowed us to observe that the architects have basic knowledge on this subject, but require help to improve and achieve that their image, positioning and sales gradually increase to such a degree that they can consolidate in the labor market. Finally,